HIJRAH’ OF THE MIND NEEDED TO ATTAIN SUCCESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 19 October 2015 – In order for Universiti Sains Malaysia (USM) to attain success in the future, its community needs to do a ‘hijrah’ (shift) of the mind in totality and in togetherness.